THE IMPACT OF ADVERTISING TOWARDS BRAND IMAGE AND PURCHASE INTENTION: THE CASE STUDY OF MATAHARIMALL.COM - Dewi, Irra Chrisyanti; Hartono, Jordy (Review of Management and Entrepreneurship, 2019)
The purpose of this study was to determine whether the advertising impacts brand image and purchase intention. This study used purposive sampling because it is adaptable and suited to the research objectives. The validity and reliability had been tested. Hypothesis testing used Structural Equation Modeling. The results were (1) advertising (X1) has an effect on brand image (Y1) with the value of Critical Ration brand image is 5.776 with a probability of less than 0.05, (2) advertising (X1) have no significant effect on purchase intention (Y2) with Critical Ration value of 1.052 and a probability 0.293, and (3) brand image (Y1) has an effect on purchase intention (Y2) with the value of Critical Ration of 4.174 and a probability value of less than 0.05.